1990
DOI: 10.3171/jns.1990.73.1.0018
|View full text |Cite
|
Sign up to set email alerts
|

The International Cooperative Studyon the Timing of Aneurysm Surgery

Abstract: The International Cooperative Study on the Timing of Aneurysm Surgery evaluated the results of surgical and medical management in 3521 patients between December, 1980, and July, 1983. At admission, 75% of patients were in good neurological condition and surgery was performed in 83%. At the 6-month evaluation, 26% of the patients had died and 58% exhibited a complete recovery. Vasospasm and rebleeding were the leading causes of morbidity and mortality in addition to the initial bleed. Predictors for mortality i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
168
3
10

Year Published

1993
1993
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 1,735 publications
(185 citation statements)
references
References 56 publications
4
168
3
10
Order By: Relevance
“…Reports on the overall outcome of SAH can be classified broadly into those from epidemiological studies and those from referral centers or large-scale cooperative studies, but differences between them are apparent [2, 12, 13, 17, 30, 31, 32, 33, 39, 40, 41, 42, 43, 44]. According to community-based studies other than that from Izumo, 3–21% of patients with SAH died before receiving medical attention [45]and overall case fatality rates were 15–42% in the first week [1, 8, 11, 15, 25, 43], 33–54% at 3 weeks [2, 11, 46, 47], 20–61% at 1 month [8, 10, 11, 12, 13, 14, 16, 25, 30, 31, 32, 33, 39, 42, 43, 44, 48, 49, 50, 51], 29–44% at 6 months [11, 14, 52]and 33–77% at 1 year [8, 11, 25, 30, 39, 42, 44, 48].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Reports on the overall outcome of SAH can be classified broadly into those from epidemiological studies and those from referral centers or large-scale cooperative studies, but differences between them are apparent [2, 12, 13, 17, 30, 31, 32, 33, 39, 40, 41, 42, 43, 44]. According to community-based studies other than that from Izumo, 3–21% of patients with SAH died before receiving medical attention [45]and overall case fatality rates were 15–42% in the first week [1, 8, 11, 15, 25, 43], 33–54% at 3 weeks [2, 11, 46, 47], 20–61% at 1 month [8, 10, 11, 12, 13, 14, 16, 25, 30, 31, 32, 33, 39, 42, 43, 44, 48, 49, 50, 51], 29–44% at 6 months [11, 14, 52]and 33–77% at 1 year [8, 11, 25, 30, 39, 42, 44, 48].…”
Section: Discussionmentioning
confidence: 99%
“…It has been well established that the management outcome depends on the clinical grading [7, 20, 24, 25, 27, 41], age [3, 7, 13, 19, 20, 22, 24, 27, 28, 29, 41], rebleeding [7, 21, 23], SAH on CT scans [7, 41], the timing of admission [20, 22]and the aneurysm site [7, 41], associated with survival of patients with ruptured aneurysms. However, there have been few community-based studies dealing with predictors of outcome in patients with SAH [7, 12, 24].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Non-contrast CT scanning is the investigation of choice. If performed within 48 h, it will identify SAH in 90-95% of cases [31,32]. Characteristic high density (white) areas are seen within the basal cisterns (Fig.…”
Section: Initial Management In the Emergency Departmentmentioning
confidence: 99%
“…This treatment mode produced a favorable result in 3.8-18% of cases, with a mortality rate of 68-87.4%. Later in early 1990s, several clinical reports indicated that early aggressive medical and surgical treatment could lead to better outcomes, with success rates that ranged from 7% to 42.6% 3,4,6,7 . With hundreds of varieties of aneurysm clips in different shapes and sizes, surgical clipping has been the gold standard for the treatment of both ruptured and unruptured cerebral aneurysms since the 1960s due to the the mechanical complexity of existing clips as well as the emergence of the operating microscope.…”
mentioning
confidence: 99%